Proposed Education Quality Improvement Using the Analytical Hierarchy Process (AHP) and the Poka-yoke Method at SDS Kartini (Case Study: Grade I and Grade II) - Wijaya, Felicia; Abidin (International Journal of Industrial Engineering and Engineering Management, 2024)
Since everything in this world is mortal and ultimately ends, life here is valuable for making a positive contribution. Early in life, one must obtain an educational or learning process to contribute positively. SDS Kartini is a service industrial institution in the basic education field, which consists of six levels or grades. However, in the implementation, the development of students in grades I and II at SDS Kartini is still less than optimal. Next, since human resources are mostly involved in the learning process performances, the poka yoke method is used to prepare the improvement solution. Then, at the procedure of the poka yoke method, there is a stage for choosing the best solution. The analytical hierarchy process (AHP) method can be applied to determine the best solution. Based on the opinions of several education practitioners (class teacher, Chairman of Foundation, and school accreditation assessor) and the calculations using the analytical hierarchy process (AHP) method, the best solution obtained is that the teacher must establish good relationships with the parents or guardians of the students. To reach that goal, a standard operating procedure (SOP) or workflow focused on optimizing attendance records has been proposed. That proposed solution is named "HADIR", where "HADIR" stands for harmonization, assistance, declaration, inspection, and repetition.